Cardiorespiratory Fitness and Performance in Multiple Domains of Executive Functions in School–Aged Adolescents - Cabral, Ludmila Lucena Pereira; Browne, Rodrigo Alberto Vieira; Freire, Yuri Alberto; Schwade, Daniel; Souto, Gabriel Costa; Dantas, Matheus; Lima, Flávio Anselmo Silva; Farias-Junior, Luiz Fernando; Costa, Eduardo Caldas; Barros, Jônatas França (Frontiers in Physiology, 2021)
The objective of this study was to investigate the association between cardiorespiratory fitness (CRF) and performance in multiple domains of executive functions in school–aged adolescents. A sample of 132 adolescents (43% girls) aged 11‒16 years were included in this cross–sectional study. Each participant completed a progressive aerobic cardiovascular endurance running (PACER) test, computerized cognitive tasks (Attentional Network, Berg’s Card Sorting, Go/No–Go oddball, Sternberg’s Working Memory, and Tower of London) and questionnaire for daytime sleepiness, as well as other factors that might influence cognitive performance (age, sex, school year, pubertal stage and body mass index – BMI). Generalized linear model was used to calculate the coefficient estimates (β) and its 95% confidence interval (CI) for the cognitive tasks using PACER laps as a predictor, controlling for potential confounding variables. There was a negatively association of PACER laps with planning (β= –17.1, 95% CI –31.9, –2.3) and solution (β= –44.6, 95% CI –75.1, –14.2) time in performing the Tower of London task, as well as with perseverative errors in performing Berg’s task (β= –0.073, 95% CI –0.133, –0.013). Moderating effect of sex was found for the association of PACER laps with completed categories and perseverative errors in Berg’s task (p < 0.05). Mediating effect of BMI was found for the association between PACER laps and NoGo task, revealing a full mediator accounted for 81% of the total effect mediated (standardized indirect effect, –0.069, 95% CI –0.140, –0.020; standardized direct effect, 0.011, 95% CI –0.149, 0.165). No association was found for Attentional or Sternberg’s tasks. The findings suggest that school–aged adolescents with higher CRF level showed better planning and problem–solving abilities and cognitive flexibility. Besides, the positive association of CRF with cognitive flexibility was sex–moderated and with inhibitory control was BMI–mediated.